2017
DOI: 10.1039/c7sc01674c
|View full text |Cite
|
Sign up to set email alerts
|

Mono-N-protected amino acid ligands stabilize dimeric palladium(ii) complexes of importance to C–H functionalization

Abstract: C–H activation, C–H functionalization, cyclopalladation, mono-protected amino acid, dimeric Pd amino acid complexes, MPAA coordination, relay of stereochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 68 publications
10
54
1
1
Order By: Relevance
“…An unusual ligand combination of readily available quinoxaline and N-acetyl-Lalanine (Ac-Ala-OH) [62][63][64][65][66][67][68] proved uniquely suitable with ferricyanate as cyanide donor to effect direct cyanation of arenes (Table 1, see also Tables S1-S8). Our goal was to provide a sufficiently stable and reactive Pd(II) center for metalation (amino acid ligand), combined with a second ligand that is sufficiently coordinating to prevent catalyst deactivation by cyanide ligation, and at the same time does not inhibit the electrophilicity for metalation (quinoxaline).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An unusual ligand combination of readily available quinoxaline and N-acetyl-Lalanine (Ac-Ala-OH) [62][63][64][65][66][67][68] proved uniquely suitable with ferricyanate as cyanide donor to effect direct cyanation of arenes (Table 1, see also Tables S1-S8). Our goal was to provide a sufficiently stable and reactive Pd(II) center for metalation (amino acid ligand), combined with a second ligand that is sufficiently coordinating to prevent catalyst deactivation by cyanide ligation, and at the same time does not inhibit the electrophilicity for metalation (quinoxaline).…”
Section: Resultsmentioning
confidence: 99%
“…64,81,82 MPAA ligands have been shown to be effective in Pd-catalyzed C-H functionalization. [62][63][64][65][66][67][68] Previous reports have shown that the displacement of acetate in Pd(II) complexes by MPAA is facile. 66,68 Considering the fact that Pd(II) and quinoxaline or Pd(II) and amino acid alone could not effect cyanation, it is plausible to assume that the active Pd catalyst in the cyanation reaction features a bidentate amino acid ligand and a monodentate quinoxaline ligand.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Musaev, Lewis et al thoroughly examined the effects of mono-N-protected amino acids (MPAA) in the C-H activation of dimethylbenzylamines (DMBA-s) (Scheme 3). 16 The binuclear complexes 9 analogous to 8 containing bridging MPAA instead of acetates were synthesized. Furthermore, it was shown that these dimeric complexes in the presence of iodobenzene dichloride undergo subsequent C-H functionalization to give other chlorinated dimeric palladacycles 10.…”
Section: Binuclear Speciesmentioning
confidence: 99%